Sistem Rekomendasi Desain Jersey Menggunakan Metode Item Based Collaborative Filtering - mohammad amiril fauzi; Umi Chotijah; Henny Dwi Bhakti (Universitas Muhammadiyah Gresik, 2021)
Creative Color Gresik is a convection company engaged in the production of jersey making which is located in the city of Gresik, East Java. The production carried out is jersey printing for sports clothes to clothes for the team. The problem that is obtained after observing is the customer who wants to order a jersey at PT. Creative Col-or Gresik still doesn't have a picture of the jersey he wants to make. The number of designs that exist in PT. Creative Color Gresik, makes customers feel confused in making choices. Each design has a different motif and color. The development of a jersey design recommendation system using the item based collaborative filtering method can assist in providing jersey design recommendations that can assist customers in determining the design to be made according to the results of the recommendations generated. The test results of the item based collaborative filtering method using questionnaire testing obtained an accuracy of 75% and an error of 25%.